Comparison of Deep and Moderate Neuromuscular Blockade on Intestinal Mucosal Barrier in Laparoscopic Gastrectomy: A Prospective, Randomized, Double-Blind Clinical Trial - Huang, He; Zhou, Ling; Yu, Yingying; Liu, Shijiang; Xu, Hao; Xu, Zekuan; Yang, Chun; Liu, Cunming (Frontiers in Medicine, 2022)
Deep neuromuscular blockade (NMB) improves the surgical conditions and is benefit for the postoperative recovery after laparoscopic surgery. However, the mechanisms of deep NMB in promoting the recovery of intestinal function have not been completely investigated. The objective of our study was to determine the impact of the deep NMB and moderate NMB strategy on the intestinal barrier function after laparoscopic gastrectomy. We collected patients undergoing elective laparoscopic gastrectomy. Patients were randomized to deep NMB (post-tetanic count 1–2) vs. moderate NMB (train-of-four count 1–2) during the surgery. Primary outcomes were time to flatus, serum diamine oxidase (DAO) and D-lactate, and gut microbiota. Other outcomes were surgical condition scores, postoperative visual analog pain scores, and length of hospital stay. Ninety patients in deep NMB group and sixty patients in moderate NMB group completed the study. Main results showed that the time to flatus was decreased in deep NMB group (74 ± 32 h) than that in moderate NMB group (93 ± 52 h, P = 0.006). The level of serum D-lactate was statistically increased in the moderate NMB group than that in the deep NMB group (1,209 ± 224 vs. 1,164 ± 185 ng/ml, p < 0.001). But no significant differences could be detected in the level of DAO between the groups. Additionally, the 16s rRNA analysis indicated that gut microbiota were similar in Alpha diversity but distinct in Beta diversity. Furthermore, the beneficial bacteria, such as genus Lactobacillus and Bifidobacterium, were more abundant in the deep NMB group, while the potentially harmful bacteria were more abundant in the moderate NMB group. Our findings suggested that the intestinal mucosal barrier and gut microbiota were better preserved in deep NMB, which greatly improved the postoperative recovery of intestinal function after laparoscopic gastrectomy.